2017
DOI: 10.1038/ijo.2017.178
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable risk factors in the first 1000 days for subsequent risk of childhood overweight in an Asian cohort: significance of parental overweight status

Abstract: Early-life risk factors added cumulatively to increase childhood adiposity and risk of overweight/obesity. Early-life and preconception intervention programmes may be more effective in preventing overweight/obesity if they concurrently address these multiple modifiable risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 55 publications
6
44
0
Order By: Relevance
“…We presented models adjusting for confounding variables, such as maternal ethnicity, maternal education level, maternal pregnancy BMI at ≤14 weeks gestation, child sex, child’s birth order and breastfeeding duration. These confounders were chosen for this analysis based on the associations with the exposure of maternal feeding practices [ 22 ], and outcomes of dietary intake and BMI[ 25 , 35 ] as previously reported from our studies using the GUSTO cohort. The graphical presentation of confounding in a directed acyclic graph(DAG) is available in S1 Fig .…”
Section: Methodsmentioning
confidence: 99%
“…We presented models adjusting for confounding variables, such as maternal ethnicity, maternal education level, maternal pregnancy BMI at ≤14 weeks gestation, child sex, child’s birth order and breastfeeding duration. These confounders were chosen for this analysis based on the associations with the exposure of maternal feeding practices [ 22 ], and outcomes of dietary intake and BMI[ 25 , 35 ] as previously reported from our studies using the GUSTO cohort. The graphical presentation of confounding in a directed acyclic graph(DAG) is available in S1 Fig .…”
Section: Methodsmentioning
confidence: 99%
“…4,36 Previous studies suggest that the common risk alleles for obesity are associated with increased appetite and reduced satiety, and appropriate diet may be helpful in limiting or offsetting a genetic predisposition to obesity. [37][38][39] Recent studies further suggested that physical activity attenuated the effect of the obesity risk allele on the odds of obesity (27%) and on the odds of overweight (26%) in children, which may work through modified physiological mechanisms (elevated blood circulation, increased levels of neurotrophins, and neurotransmitters) that caused more energy consumption. 2,14,40,41 However, what roles the gene-environment interaction play in both cellular and molecular levels that remains to be explored.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Table 2 summarized and quantified the association between five peculiar interrelated behaviors, and overweight and obesity. We decided to look at parental overweight status before pregnancy, cesarean delivery, early infant feeding, short sleep duration, and physical activity, because these could be the five effective behaviors that play a role in pediatric overweight and obesity development [ 28 , 88 , 89 , 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…This association is primarily related to the effect of lower diet quality on the body fat compartment of neonate, and this result is confirmed when the infant body fat is measured using precise and accurate body composition techniques [ 27 ]. Aris et al showed that paternal overweight status [95% CI: 9.6–11.6] had a large individual predicted probability of child overweight/obese [ 28 ]. In light of these findings, early-life and preconception intervention programs may be more effective in preventing overweight and obesity occurring later in life [ 28 ].…”
Section: Practice One: Both Mother and Father Behavior Are Importamentioning
confidence: 99%
See 1 more Smart Citation